Taste Beyond the Trend: How Service Quality Drives Customer Loyalty in Malaysia’s Fast-Service F&B Sector - Jamin Kun Peng Xia; Louis Yong Yu Lee; Meenu Baliyan; Yeok Teng Chong; Zhiheng Chen; Cherry Lee Chee Chong; Zheng Hung Chin; Alif Aminullah; Sachin Kumar; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
This study investigates the impact of service quality dimensions on customer satisfaction and loyalty in Malaysia’s fast-service food and beverage (FB) sector, focusing on Mixue outlets. Guided by the SERVQUAL framework, the research aims to identify which service dimensions most strongly influence satisfaction and how these effects extend to customer loyalty. Data were collected through a survey of 99 Mixue customers, assessing five service quality dimensions: tangibles, reliability, responsiveness, empathy, and assurance, alongside satisfaction and loyalty indicators. Using regression analysis, the model explained 81.1% of the variance in satisfaction and 78.8% in loyalty. Tangibles (? = 0.208, p 0.01), reliability (? = 0.372, p 0.01), empathy (? = 0.280, p 0.01), and assurance (? = 0.220, p 0.05) significantly affected satisfaction, while only assurance directly influenced loyalty (? = 0.739, p 0.001). Satisfaction also positively affected loyalty (? = 0.275, p 0.05), confirming its mediating role. The findings highlight that while multiple service elements enhance satisfaction, loyalty is primarily driven by psychological trust and staff competence. These insights underscore the importance of assurance-based training, customer feedback monitoring, and standardized service accreditation to strengthen long-term loyalty in youth-oriented FB markets.